(untitled) (Journal of the College of Basic Education, 2026)
This research aims to study the semantic structure and rhetorical style in Bediüzzaman Said Nursi’s "Isharat al-I’jaz fi Mazan al-Ijaz," analyzing them in light of modern linguistics and demonstrating their impact on the foundation of jurisprudential and legal principles. The research employs a critical analytical, descriptive-analytical, and comparative methodology. The research revealed the distinctiveness of Nursi’s approach, characterized by its conscious integration of linguistic analysis and legal foundations. He employed modern linguistic theories, such as semantic fields, displacement, and context, in analyzing the Qur’anic text. The research also demonstrated how Nursi contributed to the renewal of Islamic jurisprudence (Usul al-Fiqh) by presenting an applied model for deriving general legal principles through the study of semantic structure and rhetorical framework. The research is divided into four main chapters. The first addresses the theoretical and methodological framework, the second analyzes the semantic structure, the third examines the rhetorical framework, and the fourth focuses on the impact on establishing legal principles and renewing jurisprudence. The research reached significant conclusions that affirm the originality and modernity of Nursi’s approach, demonstrating that his efforts represent a bridge between tradition and modernity, combining traditional authenticity with a contemporary vision and making a prominent contribution to the renewal of Qur’anic and legal studies. The research recommends paying close attention to Nursi’s approach in contemporary Qur’anic studies, employing the linguistic method in renewing Islamic jurisprudence, and conducting further comparative studies with Western methodologies in text analysis